New challenges for education in agroecology. Issue 6 (3rd July 2018) - David, Christophe; Bell, Michael M
ABSTRACT: Based on discussions in a workshop associated with the conference The Agroecological Imagination: A Franco-American Exchange, we synthesize the state of agroecological education. We focus on three central questions: the what, how, and who of agroecological education. What are the key competencies, skills, and attitudes for future agroecologists? How do we best teach and learn agroecology? Who the learners and teachers are and should be? With regard to the what, we offer the notion of the expert-generalist who has an expertise but is also trained in integrative and transdisciplinary thinking. With regard to the how, we emphasize the importance of experiential learning and action learning, or active experience, and process for content in context. With regard to the who, we discuss the centrality of recognizing the broad community of agroecology, and the importance of agroecological education reflecting that breadth.